EXPERIMENTAL INVESTIGATION ON EFFECT OF AG-WATER NANOFLUID ON THE THERMAL PERFORMANCE OF HEAT PIPE - ZINN LYNN, THAW (2018)
Heat pipes are used as heat exchangers to control the increase in unwanted heat load of certain equipment with the help of self-contained design by two-way flow working fluid. In this project, thermal performance changes of heat pipe have been studied by using deionized water based nanofluids and acetone based nanofluids. The copper nanoparticles those have diameter of 50 nm are tested in this project by mixing with base fluids. For the preparation process of nanofluids, magnetic stirring device and ultrasonic cleaner are used. Two different volume concentrations (0.5 % and 1 %) of nanofluids have been tested and thermal performance changes of heat pipe have been investigated. Effect of different input powers and nanoparticles concentrations on heat transfer coefficient and thermal resistance of heat pipe is investigated. Moreover, effect of different angles of inclinations on thermal performance properties of heat pipe is examined and average temperature distribution of the heat pipe is recorded too. From the experimentations, nanoparticles have significant effect on thermal performance according to the results. When the effect of different input power to the performance heat pipe is investigated, thermal resistance decreases, and heat transfer coefficient increases with the increase in value of input powers. For the effect of different angles of inclinations of heat pipe by using deionized water based nanofluids, thermal resistance seems to decrease, and heat transfer coefficient tend to increase and found out that 75-degree angle is the best for thermal performance. However, for acetone based nanofluids, the best thermal performance angle is 45-degree angle.